The Effectiveness of Utilizing the Kaizala Application in Online Mathematics Learning in The Middle of a Pandemic In First High School Students - Humairah, Yulia; Elfrianto, Elfrianto (Jurnal Riset Ilmu Pendidikan, 2022)
This study aims to determine the effectiveness of the Kaizala application in online mathematics learning in the midst of a pandemic on the interest in learning mathematics of class IX students of MTsS Bary Tarbiyah. This study uses descriptive qualitative research methods. The data collection method used is by conducting observations, interviews, and documentation. The sources of data in this study are: grade IX students and Mathematics Teacher at MTsS Bary Tarbiyah. The results obtained related to the effectiveness of the use of the Kaizala Application in online Mathematics learning in the midst of a Pandemic on students' interest in learning mathematics, namely from the 12 responses received by researchers there were around 80% which stated that the online learning process by utilizing the Kaizala Application was running effectively because this was an application. which is easy to use, does not require a lot of quota to access it compared to other applications